2014
DOI: 10.1179/1362171813y.0000000167
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties in friction stir weld of 12Cr steel

Abstract: Friction stir welding was employed for joining of 12Cr heat resistant ferritic steel. Microstructure and mechanical properties in the obtained welds were examined and their relationship was established. The stir zone microstructure was found to consist of quenched martensite with numerous fine dispersoids uniformly distributed in grain interiors. The formation of this microstructure remarkably strengthened the stir zone. Tempering for 3?6 ks at 923 K reduced the as welded hardness of friction stir weld to near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Further analysis was made to study each strengthening effect for FSSPed steels. Several investigations have been conducted to estimate the dominant factor on the mechanical properties of thermomechanical processing, such as FSW [ 19 , 20 , 21 , 22 , 33 ] for steels. Mazaheri et al estimated the yield stress of ultra-FG DP steel by accumulating each strengthening effect [ 22 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis was made to study each strengthening effect for FSSPed steels. Several investigations have been conducted to estimate the dominant factor on the mechanical properties of thermomechanical processing, such as FSW [ 19 , 20 , 21 , 22 , 33 ] for steels. Mazaheri et al estimated the yield stress of ultra-FG DP steel by accumulating each strengthening effect [ 22 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Li et al found that the lower hardening capacity (the ratio of the ultimate tensile strength to the yield strength) of FSPed reduced-activation ferritic/martensite (RAFM) steel due to grain refinement strengthening effect based on the Hall-Petch relationship and dislocation strengthening effect [ 20 ]. Hua et al explained that the hardenability of FSWed 12Cr steel was consistent with grain refinement, carbon content, and the existence of dispersoids [ 21 ]. Also, they observed grain refinement in the SZ through EBSD.…”
Section: Introductionmentioning
confidence: 99%
“…If the distribution of fine MX particles is inhomogeneous in the weld, effect of MX particles on hardness profile in the PNC-FMS side of the weld shall be considered. However, it seems more likely that such hardening by MX particles would be uniform in the PNC-FMS side of the weld, as shown in a previous paper on a friction stir weld of 12 pct Cr steel, [53] because the dissolution temperature of the MX particles was higher than the expected maximum temperature during FSW.…”
Section: Mechanical Propertiesmentioning
confidence: 92%
“…The available solution to overcome these issues is Hybrid Friction Stir Welding. The Hybrid Friction Stir Welding means an additional heating source is attached to the FSW for in situ heating process [20][21][22]. The investigations on hybrid FSW show that it can improve joint strength and enhance the tool life [23−25].…”
Section: Introductionmentioning
confidence: 99%